Verbal fluency in normal aging and cognitive decline: Results of a longitudinal study. (July 2021) - Frankenberg, Claudia; Weiner, Jochen; Knebel, Maren; Abulimiti, Ayimunishagu; Toro, Pablo; Herold, Christina J.; Schultz, Tanja; Schröder, Johannes
Highlights: Phonematic verbal fluency is a predictor of cognitive decline and seems to be useful for computerized dementia screening. Phonematic verbal fluency deficits occur even in young old age and precedes marked cognitive decline years before. Phonematic verbal fluency is associated with important acoustic rather than lexical features of spoken language which can directly be inferred from recordings of spontaneous speech. Abstract: Verbal fluency – i.e. the ability to name as many words of a given category as possible in a defined time interval – is an integral part of neuropsychological test batteries for the diagnosis of dementia. Verbal fluency can be easily administered and thus may also be implemented in computerized dementia screening tests. In the present study we sought to investigate the capability of phonemic verbal fluency as a potential predictor of cognitive decline and its associations with acoustic and lexical features directly inferred from recordings of spoken language. Data from 246 ILSE participants born in the years 1930 to 1932 were included. Subjects were investigated three times (t1-t3) over a period of more than 10 years by two board certified geriatric psychiatrists: the mean age of the sample was 62.77 at t1, 66.36 at t2, and 74.22 at t3. To evaluate the sensitivity of phonemic fluency performance on cognitive impairment, scores obtained at t1 and t2 were compared with repeated measures ANOVA between subjects who were cognitively intact and those who were diagnosed with mild cognitive impairment (MCI) or Alzheimer's dementia (AD) at t3. In addition, acoustic and lexical features of spoken language were extracted with automatic speech recognition from semi-structured autobiographical interviews recorded at baseline. Scores were correlated with verbal fluency performance at t1. In all analyzes education was considered as a covariate. Regarding verbal fluency obtained at t1 and t2, repeated measures ANOVA revealed significantly higher scores between subjects who were cognitively intact (HC) at t3 compared with those diagnosed with MCI or AD at t3. At baseline verbal fluency was significantly correlated with important acoustic features of spontaneous speech: word rate, phoneme rate, speech-duration and silence-to-word-ratio. Verbal fluency deficits were proven already in young old age and precede marked cognitive decline years before in a large group recruited from the general population. Verbal fluency is associated with acoustic rather than lexical features of spoken language which can directly be inferred from spontaneous speech.